Effect of boron and water-to-cement ratio on the performances of laboratory prepared Belite-Ye'elimite-Ferrite (BYF) cements - Pérez-Bravo, Raquel; Morales-Cantero, Alejandro; Bruscolini, Marguerita; García-Aranda, Miguel Ángel; Santacruz-Cruz, María Isabel; Gómez-de-la-Torre, María de los Ángeles (My University, 2021)
The effect of superplasticiser, borax and the water-to-cement ratio on BYF hydration and mechanical strengths has been studied. Two laboratory-scale BYF cements—st-BYF (with -C2S and orthorhombic C4A3 S) and borax-activated B-BYF (with a’H-C2S and pseudo-cubic C4A3s) have been used, and both show similar particle size distribution. The addition of superplasticiser and externally added borax to BYF pastes has been optimised through rheological measurements. Optimised superplasticiser contents (0.3, 0.4 and 0.1 wt%for st-BYF, B-BYF and st-BYF with externally added 0.25 wt % B2O3, respectively) result in low viscosities yielding homogeneous mortars. The calorimetric study revealed that st-BYF is more reactive than B-BYF, as the values of heat released are 300–370 J/g and 190–210 J/g, respectively, after 7 days of hydration; this fact is independent of the water-to-cement ratio. These findings agree with the higher degree of hydration at 28 days of b -C2S in st-BYF (from 45 to 60%) than a’H-C2S in B-BYF (~20 to 30%). The phase assemblage evolution has been determined by LXRPD coupled with the Rietveld method and MAS-NMR. The formation of stratlingite is favoured by increasing the w/c ratio in both systems. Finally, the optimisation of fresh BYF pastes jointly with the reduction of water-to-cement ratio to 0.40 have allowed the achieving of mortars with compressive strengths over 40 MPa at 7 days in all systems. Moreover, the st-BYF mortar, where borax was externally added, achieved more than 70 MPa after 28 days. The main conclusion of this work does not support Lafarge’s approach of adding boron/borax to the raw meal of BYF cements. This procedure stabilises the alpha belite polymorph, but its reactivity, in these systems, is lower and the associated mechanical strengths poorer.
Keywords: Materiales; Cemento; Rietveld; Cement hydration; Ecocements